2009
DOI: 10.1128/jvi.00245-09
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the PI3K/Akt Pathway Early during Vaccinia and Cowpox Virus Infections Is Required for both Host Survival and Viral Replication

Abstract: The family Poxviridae is a family of large, linear, doublestranded DNA viruses that carry out their entire life cycle within the cytoplasmic compartment of infected cells. Vaccinia virus (VACV) is a prototypical member of the genus Orthopoxvirus, which also includes the closely related cowpox virus (CPXV) (12, 52). The genomes of these viruses are approximately 200 kbp in length, with a coding capacity of approximately 200 genes. The genes involved in virus-host interactions are situated at both ends of the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
105
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 94 publications
(143 reference statements)
11
105
0
2
Order By: Relevance
“…Our RNAi screen indicated that PI(3)K, PI(4)K, PI(5)K and PIKfyve were needed for MV infection (Figure 2). Previous studies have demonstrated a role for PI(3)K during multiple stages of VACV infection 68, 69 including entry 34, 39, 70. Consistent with this, PtdIns(3)P was detected on early MV‐containing macropinosomes until 30 min suggesting that these compartments undergo a lipid switch during their maturation (Figure 4A,B).…”
Section: Discussionsupporting
confidence: 82%
“…Our RNAi screen indicated that PI(3)K, PI(4)K, PI(5)K and PIKfyve were needed for MV infection (Figure 2). Previous studies have demonstrated a role for PI(3)K during multiple stages of VACV infection 68, 69 including entry 34, 39, 70. Consistent with this, PtdIns(3)P was detected on early MV‐containing macropinosomes until 30 min suggesting that these compartments undergo a lipid switch during their maturation (Figure 4A,B).…”
Section: Discussionsupporting
confidence: 82%
“…GM-CSF receptor activation is followed by Jak2 phosphorylation of receptor tyrosines and eventual activation of Stat5 and the MAPK pathways via Grb2, Shc, and SHP2 (66). Similarly, VACV is reported to be dependent on MAPK signaling for replication (45,46,47). We observed significantly decreased viral production with treatment of Akt and Erk inhibitors (Fig.…”
Section: Discussionsupporting
confidence: 47%
“…VACV is dependent on Akt and Erk1/2 signaling pathways for entry and replication (45)(46)(47)(48). Since we have discovered that M1 and M2 cells are permissive to VACV, we sought to analyze the dependence of these two pathways on VACV replication in MDMs independent of binding and entry.…”
Section: Resultsmentioning
confidence: 99%
“…Vaccinia virus is known to manipulate hostsignalling pathways, such as MAPK (3) and Akt (38,39) pathways, to enhance viral replication. Using a kinase array, we showed that infection with GLV-1h68 activated JNK pathways in both V600E BRAF mutant and BRAF/RAS wild-type cells.…”
Section: Discussionmentioning
confidence: 99%